2015
DOI: 10.4236/ajps.2015.616259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Concentrations of Orange Juice for in Vitro Regeneration and Multiplication of Cocoyam (Taro)

Abstract: Taro (Colocasia esculenta) and tannia (Xanthosoma sagittifolium) are commonly referred to as cocoyam in Nigeria. They are cherished for their rich taste, nutritional and medicinal properties. Traditionally, cocoyams are vegetatively propagated from tuber fragments, a practice that encourages pathogen distribution. For rapid multiplication and production of quality planting materials, tissue culture technology offers promising alternative compared to the traditional production methods. In this study different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There ficant differences among the concentrations in of callus induction after four weeks of culture. The most appropriate concentrations for callus induction and somatic in these varieties were 4mg/L nd 7mg/L picloram.. A number of studies have shown that picloram and 2,4-D are the growth regulators used most frequently to induce callus formation and embryogenesis Wongtiem et 2011;Ubalua and Mbanaso, 2014). primary somatic embryos r subsequent germination into plantlets requisite to the production of large numbers of plantlets.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…There ficant differences among the concentrations in of callus induction after four weeks of culture. The most appropriate concentrations for callus induction and somatic in these varieties were 4mg/L nd 7mg/L picloram.. A number of studies have shown that picloram and 2,4-D are the growth regulators used most frequently to induce callus formation and embryogenesis Wongtiem et 2011;Ubalua and Mbanaso, 2014). primary somatic embryos r subsequent germination into plantlets requisite to the production of large numbers of plantlets.…”
Section: Discussionmentioning
confidence: 98%
“…By 28 days after inoculation, significant number of the explants formed callus in all the cassava varieties were significant differences among the genotypes, type and auxin concentrations in the frequency of callus induction after four weeks of culture. The most appropriate concentrations for callus induction and somatic embryogenesis in these varieties were 2,4-D and 7mg/L picloram.. A number of studies have shown that picloram and 2,4 are the growth regulators used most frequently to induce callus formation and embryogenesis in cassava (Hankoua et al, 2006;al., 2011;Ubalua and Mbanaso, 2014). Efficient induction of primary somatic embryos and their subsequent germination into plantlets is a pre-requisite to the production of large in vitro grown cassava genotypes; were used to determine the effect of different concentration callus induction and By 28 days after inoculation, significant number of the explants lus in all the cassava varieties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations